1993
DOI: 10.1038/hdy.1993.4
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of zinc contamination from electricity pylons. Genetic constraints on selection for zinc tolerance

Abstract: Zinc tolerance, based on root growth in zinc-containing solutions, was examined in samples of 30 Agrostis capillaris L. individuals collected from populations beneath five electricity pylons in North Wales. The populations were found to vary in zinc tolerance. Three of them contained individuals whose tolerance ranged from low to high, one population consisted of individuals with low to moderate tolerance, whilst the fifth population (ZK-180) contained no tolerant individuals. Differences in zinc tolerance wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 9 publications
2
49
0
Order By: Relevance
“…This variation is highly heritable. Al-Hiyaly et al (1993) showed there to be a realized heritability of about 40 °o for Zn tolerance in three A. capillaris populations from beneath electricity pylons, and remarkably Macnair, et al (1993) have found exactly the same value for the heritability of the within-mine variation of Cu tolerance in M. guttatus at Copperopolis. Rocovitch & West (1975) found a correlation between As content of the soil and arsenate tolerance of plants at the individual level, and Macnair (1987i) details a number of other similar examples.…”
Section: The Spatial Distribution Of Tolerance In Contaminated Sitesmentioning
confidence: 85%
See 1 more Smart Citation
“…This variation is highly heritable. Al-Hiyaly et al (1993) showed there to be a realized heritability of about 40 °o for Zn tolerance in three A. capillaris populations from beneath electricity pylons, and remarkably Macnair, et al (1993) have found exactly the same value for the heritability of the within-mine variation of Cu tolerance in M. guttatus at Copperopolis. Rocovitch & West (1975) found a correlation between As content of the soil and arsenate tolerance of plants at the individual level, and Macnair (1987i) details a number of other similar examples.…”
Section: The Spatial Distribution Of Tolerance In Contaminated Sitesmentioning
confidence: 85%
“…Not all species that exhibited Zn tolerance were present at each pylon. The difference appears to be in the local populations surrounding the pylons; those that had a low frequency of tolerance genes could produce a tolerant population under the pylon, while those that did not, could not (Al-Hiyaly et al, 1993).…”
Section: The Occurrence Zvithin Normal Populationsmentioning
confidence: 99%
“…Major genes contribute to some examples of metal tolerance and must be present within populations for selection to occur (Macnair, 1993). Studies have demonstrated that some plant populations will evolve metal tolerance at some sites and not others (Al-Hiyaly et al, 1993). As rare genes will not be present in all small populations, large populations or a large number of populations will need to be treated to select for these rare genes.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of such forms of plants, which have the capacity to grow and reproduce effectively in areas with increased metal content in the soil, has usually ranged from a few dozen to several decades [65][66][67]. It should be noted, however, that the adaptations disclosed in these populations concerned only the physiological adjustment to the increased metal concentration.…”
Section: Taxonomic Rank Of Waste Heap Population -Biscutella Laevigatmentioning
confidence: 99%